2013
DOI: 10.1038/srep03512
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel modifiers of Aβ toxicity by transcriptomic analysis in the fruitfly

Abstract: The strongest risk factor for developing Alzheimer's Disease (AD) is age. Here, we study the relationship between ageing and AD using a systems biology approach that employs a Drosophila (fruitfly) model of AD in which the flies overexpress the human Aβ42 peptide. We identified 712 genes that are differentially expressed between control and Aβ-expressing flies. We further divided these genes according to how they change over the animal's lifetime and discovered that the AD-related gene expression signature is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
(65 reference statements)
0
25
0
Order By: Relevance
“…Interestingly, Aβ42 activated the Toll signaling pathway, suggesting that Toll, a pattern recognition receptor (PPR), recognizes the structure of Aβ42 aggregates as a danger-associated molecular pattern (DAMP), which explains the potent inflammatory response in AD brains (Salminen et al, 2009). More recently, the Crowther lab used a transcriptomic approach to identify the mechanisms mediating Aβ42 toxicity (Favrin et al, 2013). The microarrays identified genes involved in normal aging, including oxidative stress, immune response, and protein secretion, due to high levels of Aβ42 that altered gene expression in the young flies.…”
Section: Drosophila Models Of Aβ42 Neurotoxicitymentioning
confidence: 99%
“…Interestingly, Aβ42 activated the Toll signaling pathway, suggesting that Toll, a pattern recognition receptor (PPR), recognizes the structure of Aβ42 aggregates as a danger-associated molecular pattern (DAMP), which explains the potent inflammatory response in AD brains (Salminen et al, 2009). More recently, the Crowther lab used a transcriptomic approach to identify the mechanisms mediating Aβ42 toxicity (Favrin et al, 2013). The microarrays identified genes involved in normal aging, including oxidative stress, immune response, and protein secretion, due to high levels of Aβ42 that altered gene expression in the young flies.…”
Section: Drosophila Models Of Aβ42 Neurotoxicitymentioning
confidence: 99%
“…This, together with the similarity in exon arrangement between Sod3 in Drosophila and Sod4 in C. elegans , suggests that SOD3v1 is a secreted extracellular protein, whereas SOD3v2 is membrane associated. Further evidence suggesting the two forms are functionally different is seen in the results of Favrin [ 22 ] who found that the long form RD/RE transcripts are over 10-fold more highly expressed in a Drosophila Alzheimer's model, whereas expression of the short form, RA/RB, falls off with ageing similar to the control.…”
Section: Discussionmentioning
confidence: 99%
“…The gene has since been confirmed as an extracellular SOD in a parasitic wasp [ 20 ] and in Drosophila [ 21 ]. It was also identified as one of the genes with a significant change in expression in a Drosophila model of Alzheimer's disease [ 22 ]. In mammals, extracellular SOD is highly expressed in the lung, testis, central nervous system and circulatory system [ 23 , 24 ] and is medically important through its involvement in cardiovascular disease [ 8 , 25 ] and age-related cognitive decline [ 2 , 12 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sod3 was also found to be induced in flies over-expressing the human Alzheimer's disease protein fragment Abeta, and to negatively affect survival of the mutant flies (Favrin et al 2013). …”
Section: Reduced Sod Function and Agingmentioning
confidence: 95%